Sharp Changes in Muscle Tone in Humans Under Simulated Microgravity - Amirova, Liubov E.; Plehuna, Anastasija; Rukavishnikov, Ilya V.; Saveko, Alina A.; Peipsi, Aleko; Tomilovskaya, Elena S. (Frontiers in Physiology, 2021)
A decrease in muscle tone induced by space flight requires a standardized assessment of changes to control the state of the neuromuscular system. This study is a step toward the development of a unified protocol, aimed at determining the initial effect of the presence or withdrawal of support on muscle tone, the effects of a 2-h supportlessness in Dry Immersion (DI) experiments, and the changes in muscle tone depending on the site of measurement. To perform measurements of changes in muscle tone, we used a MyotonPRO device. The list of muscles that we assessed includes: trunk – mm. deltoideus posterior, trapezius, erector spinae; leg – mm. biceps femoris, rectus femoris, tibialis anterior, soleus, gastrocnemius; foot – m. flexor digitorum brevis, tendo Achillis, aponeurosis plantaris. The study involved 12 healthy volunteers (6 men, 6 women) without musculoskeletal disorders and aged 32.8 ± 1.6 years. At the start of DI, there was a significant decrease in muscle tone of the following muscles: mm. tibialis anterior (−10.9%), soleus (−9.6%), erector spinae (−14.4%), and the tendo Achillis (−15.3%). The decrease continued to intensify over the next 2 h. In contrast, the gastrocnemius muscle demonstrated an increase in muscle tone (+7.5%) 2 h after the start of DI compared to the immediate in-bath baseline. Muscle tone values were found to be site-dependent and varied in different projections of mm. erector spinae and soleus. In previous experiments, we observed a high sensitivity of the myotonometry technique, which was confirmed in this study. To make it possible to compare data from different studies, a standardized protocol for measuring muscle tone for general use in gravitational physiology needs to be developed.